O domínio prévio à definição das palavras: crítica à proposição como lugar do sentido a partir das Investigações Filosóficas de Wittgenstein - Zunino, Tatiane Boechat Abraham (2014)
This thesis seeks to examine the hypothesis that the meaning has not in its foundation the proposition and the words. That language does not inaugurate the truth in an enunciative joint, but in a practical and comprehensive operation. Thus, through Wittgenstein's Philosophical Investigations, we seeks to explain to what extent can we speak of an ambit of birthing of sense through the analysis of learning by the ostensive teaching of words, i.e., by means of some necessary conditions for the concept acquisition. To do so, we will expose some fundamental aspects of expression learning, both through teaching and verbal learning, namely, the notion of training (Abrichten) and all possible rationality which surrounds it, as well as the ostensive definition of words, trying to defend the position that training is the condition of possibility for the ostensive definition. Thus, it would be the first way of understanding, the birth of sense. After walking this path, it is possible to speak of two levels of access to sense. We try, therefore, to present a sense opening dimension through the linguistic practice in which an expression operates, so that the importance of the ostensive teaching of words is affirmed as the opening of a previous operative field that can enable the denomination. Such field implies that the expressions emerge with its meaning in the everyday praxis previously given, to then become an empirical language and bind to the facts of the world, so that the understanding of an expression assumes, in an essential way, the previous field of language and sense.